An updated review on application of nanofluids in flat tubes radiators for improving cooling performance. (December 2020) - Arora, Neeti; Gupta, Munish
Abstract: Engineers and scientists are constantly engaged in improving the cooling performance of vehicle engine radiators to achieve the sustainable and efficient use of energy and resources. In this whole exercise, efficient tube geometry and coolant plays the crucial role for enhancing the heat exchange in the way of betterment of radiator efficiency. Owing to greater surface-to-cross-section flow area ratio of flat tubes compared to circular tubes, enhances the rate of heat transfer and also compacts the dimensions of heat exchanger. Nanofluids are the suitable coolants, contribute towards high heat transfer in radiators because of good thermal properties. This article opens with the overview of nanofluid synthesis methods, mechanisms involved in heat transfer intensification through nanofluids and reviews on nanofluids in vehicle engine cooling systems. Further, the thermo-hydraulic performance of nanofluids in flat tubes automobile radiators is discussed. The effect of nanoparticle concentration, nanofluid flow rate (or Reynolds number), nanofluid temperature and tube geometry on heat and flow characteristics is critically analysed. Nanoparticles could directly affect researchers' health and work place surroundings. Thus, it is vital to understand the impact of nanoparticles on environment and human health which is also discussed in this paper. Significant results from studied literature are summarized for ready reference. Authors endeavor to recognize some challenges and provide guidelines for essential assessment in the performance of radiators. Graphical abstract: Image 1 Highlights: Nanofluid synthesis methods and reviews on nanofluids in automotive radiators have been discussed briefly. Mechanisms behind heat transfer enhancement through nanofluids are summarized. Thermo-hydraulic performance of nanofluids in flat tubes radiators is studied. Nanoparticles impact on environment and human health is described. Challenges and future perspectives of nanofluids and flat tubes in radiators are emphasized.